IMAGE COMPARISON ON T2 QTSE LUMBAL EXAMINATION USING GRAPPA TECHNIQUE WITH AND WITHOUT MAGNETIZATION TRANSFER CONTRAST IN DEGENERATIVE DISC DISEASE CASE - Arief Apriliani, Karina Sandra; Utomo, Sri Andreani; Muhaimin; Muqmiroh, Lailatul (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: The description of Degenerative Disc Disease in MRI lumbar FSE sequence T2WI is seen as a decrease in signal intensity. Patients with cases of Degenerative Disc Disease experience severe low back pain and cannot lie supine for a long time, while MRI is very sensitive to movement. GRAPPA is a parallel imaging technique that can produce images with a fast scan time but is followed by a decreased Signal to Noise Ratio SNR value. This technique needs to be followed by setting other parameters to produce an optimal image, namely by applying Magnetization Transfer Contrast (MTC). Purpose: To compare the quality of image results on lumbar MRI examination of the sagittal T2 qTSE sequence in the case of Degenerative Disc Disease with and without MTC activation. Method: This research was conducted at the dr. Soedono Madiun from August to September 2020. A sample of 16 patients who met the inclusion criteria was taken during the study. The GRAPPA and GRAPPA+MTC technique imagery results on each sample were assessed for the image quality quantitatively based on the SNR and CNR values. Result: Based on the SNR value, the GRAPPA technique and MTC activation have a higher mean than the GRAPPA technique alone. Likewise, with the CNR value, the GRAPPA technique and MTC activation have a higher average than the GRAPPA technique alone. Conclusion: The GRAPPA technique and MTC activation can be applied in Lumbar MRI examination with cases of Degenerative Disc Disease, especially in uncooperative patients.